Javanese Values Reflected in Pengakuan Pariyem Novel Written by Linus Suryadi AG - Priyoto Priyoto; Anisa Rahmadiani (STIBA IEC JAKARTA, 2024)
This study aims to determine the values of Javanese society as reflected in Pengakuan Pariyem novel by Linus Suryadi AG. More specifically, this research is aimed to answer two problem questions, namely what the Javanese values are reflected in Pengakuan Pariyem novel.The rationality of the research is to give a better understanding of the Javanese values in Javanese. The method used in this study is a descriptive method, in the form of qualitative, with a sociological approach. In collecting the data, the writer used note-taking technique. The research applied some tools of analysis that developed in the study of literature such as Javanese Values and Cultural Studies. The result of this research brings two contributions namely theoretically and practically. From theoretically, is expected to provide more specific knowledge and information regarding Javanese values. Practically, it may provide helpful reference material for further researchers who are interested in relevant topics. The results of data analysis show that seven kinds of Javanese values are reflected in Pengakuan Pariyem novel: sungkan,halus,grapyak,isin,nrimo,polite, and humble.